Kentong Damping Sound Intensity Level Based on Kentongan Length Variations - Ellianawati Ellianawati; Muhammad An’im Arravi; Fitria Wulandari; Rofita Istiqomah (Journal of Natural Sciences and Mathematics Research, 2019)
This study aims to determine the attenuation of the sound produced by a Kentongan musical instrument based on variations in the length of the Kentongan. Data were collected in a quiet room by starting to measure the noise and atmosphere of the room. This study used Sound Meter Software with version 3.4.5 with a maximum sound intensity limit of ~ 90 dB, mobile as an intermediary. This study used Kentongan with a length of 1, 29 cm and a length of 2 that was 34.1 cm. Experiments were carried out 3 times with the first experiment without Kentongan, then Kentongan 1 and then Kentongan 2. The sound intensity produced by without Kentongan is an average of 60.08 dB, then with Kentongan 1 that is, with an average of 61.86 dB, and Kentongan 2 with an average of 56.68 dB. ©2019 JNSMR UIN Walisongo. All rights reserved.